Grover’s disease – a diagnostic and therapeutic challenge - Barańska-Rybak, Wioletta; Michajłowski, Igor; Maciejewska-Radomska, Agata; Sokołowska-Wojdyło, Małgorzata (Dermatology Review/Przegląd Dermatologiczny, 2009)
Introduction. Grover’s disease is a transient acantholytic dermatosis of unknown origin. It is a pruritic, papulovesicular eruption characterized histopathologically by acantholysis with or without dyskeratosis. The disease has occasionally been reported in patients with chronic renal failure, HIV infection and after bone marrow allotransplantation. Objective. Presentation of a case of Grover disease recalcitrant to standard therapy. Case report. A 66-yr-old male patient was admitted to our department with a 3-month history of disseminated, itchy, papular eruption on the trunk. His general condition was satisfactory. The patient was treated previously with antihistamines and topical corticosteroids with no effect. Laboratory examinations were within normal limits. In histopathology acantholytic and dyskerototic changes in the epidermis consistent with Grover’s disease were observed. The patient was treated with oral acitretin and topical corticosteroids without improvement. Skin lesions and pruritus subsided after 8 weeks of treatment with the Re-PUVA method. Conclusions. In cases of Grover’s disease resistant to standard therapies (emollients, topical corticosteroids) introduction of Re-PUVA treatment may have a beneficial effect.